Execution of Motor Vehicle Fiduciary Assurance by Debt Collector - Azhar; Hirsanuddin; Djumardin, (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to find out and analyze the validity of the execution of Fiduciary Assurance by the Debt Collector in the form of objects of motor vehicle Fiduciary Assurance associated with the Fiduciary Guarantee Act and Financial Services Authority Regulations and legal protection against Debtors in the execution of the Fiduciary Guarantee by the Debt Collector.The results showed that: The validity of the execution of the Fiduciary Guarantee by the Debt Collector on motor vehicle Fiduciary Assurance objects was associated with the Fiduciary Guarantee Act and Financial Services Authority Regulation, namely: Dept. Colecctor who did not fulfill formal juridical Article 50 Regulation of the Financial Services Authority Number 29/POJK.05/2014 concerning Business Management of Financing Companies is formal juridical disability, so that all actions taken by the Debt Collector in carrying out its duties as long as it is about the execution of fiduciary guarantees have an unauthorized or irrevocable effect. Whereas if the fiduciary guarantee is not registered then it is null and void because the fiduciary deed has a time limit for registration, null and void considered never existing. It is considered never existed because it involves object certainty, and legal protection against debtors in the execution of Fiduciary Guarantees by the Debt Collector, namely: in the form of preventive legal protection including the obligation of financial institutions to register fiduciary collateral objects and employ Debt Collectors who fulfill formal juridical requirements in accordance 50 Regulation of the Financial Services Authority Number 29/POJK.05/2014 concerning Business Operations of Financing Companies. Whereas Repressive legal protection can be in the form of errors committed by the Colector Dept. can be in the form of a matter, firstly, the business license of the Financing Company can be revoked, the second is civilly the Business Entity of the Financing Company can be compensated and the third is Criminal Debt Collector can be imposed Article 365 The Criminal Code as long as the criminal elements are fulfilled have the ability to be responsible.